THE RELATIONSHIP BETWEEN HUMAN AND NATURE AS AN ECOLOGICAL REPRESENTATION BEHIND THE SACRED MYTH OF BUMBUM - Septriani Septriani; Endrizal Endrizal (Asosiasi dosen IDEBAHASA KEPRI, 2023)
This study aims to reveal the relationship between humans and the nature as represented in the mythical narrative of a tree called the sacred of Bumbum. The background of this research is the importance of bringing back the local wisdom values of the community, especially in the old Malay villages in Riau Island, which are increasingly marginalized. As a form of folk narrative, myth is an integral part of the oral literary component. To bridge literature with people's behavior, researchers used a literary anthropological approach (Vayda, 1968). While the relationship between humans and nature could be studied with an ecological approach. This research is descriptive-qualitative in nature, namely the method used to explain the condition of a system of thought or events in the present and then make a description in a systematic, factual, and accurate manner regarding the factors, nature, and relationships between the phenomena being investigated. The ecological bond between humans and the environment is reflected through: 1) the prohibition of cutting down trees; 2) the prohibition of picking leaves and tree trunks; and 3) the prohibition of defecating around trees. These forms of prohibition reflect the ecological relations of mythical discourse, which imply existence, attachment, and concern that are not just silent but live and must be kept in harmony with one another.